“Venimmo al piè d’un nobile castello”. Un disegno di Bruno Bossi per il secentenario dantesco del 1921 - Lanzarini, Orietta (Opus Incertum, 2021)
The six-hundredth anniversary of Dante Alighieri’s death was commemorated in 1921 with a rich programme of events. Three of these had as backdrops cities deeply connected to the life of the poet: Florence, Rome and Ravenna. In the latter city, one of the key figures involved in the Dante celebrations was Ambrogio Annoni, an architect and professor at the Regio Politecnico of Milan. It was Annoni, probably, who accompanied a group of student-architects to visit the monuments of Ravenna associated with the life of Dante. Bruno Bossi, a native of Canton Ticino and at the time enrolled in the first year at the Politecnico, would have been among them. The visit to Ravenna, and the celebrations of 1921 in general, could be correlated with an unpublished drawing – an “estempore” to be created in an hour – made by Bossi in May 1921. It is the graphic transposition of a passage from Canto IV of the Inferno, transcribed in the margin of the sheet, in which a large castle is described, surrounded by seven walls, overlooking a narrow river. Bossi translates the architectural image evoked by Dante’s words into a monumental and scenographic building, from which futurist and cinematic echoes emerge. In this way, the future architect paid tribute to the valuable fortified architecture of Canton Ticino, in particular to the castles of Bellinzona, and at the same time demonstrated his early interest in the arts, cinema and theatre, which would accompany him throughout his professional career.